Defining an Industry: What is the Size and Scope of the Australian Building and Construction Industry - Gerard de Valence (Australasian Journal of Construction Economics and Building, 2011)
The analysis and understanding of the conduct and performance of an industry begins with a study of its structure. However, before analysing an industry's structure it is necessary to define the industry and identify its size, scope and scale to establish its true economic contribution. This paper discusses the size and scope of the Australian building and construction industry, firstly, from a traditional industry economics approach by firm size and business characteristics using data from three construction industry surveys done over 15 years by the ABS. Secondly, data from an industry 'cluster' perspective is shown. The objective of the paper is to compare the differences found in industry size and scope in the structure-conduct-performance approach and the alternative industry cluster approach. Each model reveals different characteristics of the industry. The conclusion finds that the building and construction industry is a case where the traditional structure-conduct-performance model cannot be easily applied. 53